Toxicity of Bioactive Compound from Endophytic Fungi Isolated from Red Ginger (Zingiber officinale var. rubrum) Utilizing Brine Shrimp Lethality Assay - Prasetyo, Angga; Sidharta, Boy Rahardjo; Hartini, Yustina Sri; Mursyanti, Exsyupransia (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2019)
Red ginger (Zingiber officinale var. rubrum) has been proven to show anticancer activity. Direct use bioactive compound from red ginger has many obstacles such as large amount of red ginger’s rhizome needed, limitation of planting area, and very long time of harvesting. Utilization of endophytic fungi from red ginger’s rhizome could be an alternative to the problems. The aims of this study were to determine bioactive compound produced by endophytic fungi and toxicity activity based on LC50. Endophytic fungi were isolated from red ginger and were identified macroscopically and microscopically. The bioactive compounds were extracted using ethanol 96%. Flavonoid test was done qualitatively, bioactive compounds were analyzed by Thin Layer Chromatography (TLC), and the toxicity test was done using Brine Shrimp Lethality Assay (BSLA). The present research found two endophytic fungi isolated from red ginger rhizome. Isolate 1 was similar to Mucor sp. and isolate 2 was similar to Trichoderma sp. Phytochemical test revealed bioactive compound extracted from the isolates were contained flavonoid. TLC analysis did not detect quercetin from the bioactive compound extracted from the isolates. LC50 values of the bioactive compound from the isolates were 2.300 and 1.747 µg/ml, respectively. The toxicological results suggest that both isolates produce non-toxic compound to Artemia salina.